Pulse Wave Velocity as Marker of Preclinical Arterial Disease: Reference Levels in a Uruguayan Population Considering Wave Detection Algorithms, Path Lengths, Aging, and Blood Pressure - Alallón, Walter; Lluberas, Ricardo; Armentano, Ricardo L.; Farro, Ignacio; Olascoaga, Alicia; Florio, Lucía; Farro, Federico; Bia, Daniel; Zócalo, Yanina; Torrado, Juan (International Journal of Hypertension, 2012)
Carotid-femoral pulse wave velocity (PWV) has emerged as the gold standard for non-invasive evaluation of aortic stiffness; absence of standardized methodologies of study and lack of normal and reference values have limited a wider clinical implementation. This work was carried out in a Uruguayan (South American) population in order to characterize normal, reference, and threshold levels of PWV considering normal age-related changes in PWV and the prevailing blood pressure level during the study. A conservative approach was used, and we excluded symptomatic subjects; subjects with history of cardiovascular (CV) disease, diabetes mellitus or renal failure; subjects with traditional CV risk factors (other than age and gender); asymptomatic subjects with atherosclerotic plaques in carotid arteries; patients taking anti-hypertensives or lipid-lowering medications. The included subjects (n=429) were categorized according to the age decade and the blood pressure levels (at study time). All subjects represented the “reference population”; the group of subjects with optimal/normal blood pressures levels at study time represented the “normal population.” Results. Normal and reference PWV levels were obtained. Differences in PWV levels and aging-associated changes were obtained. The obtained data could be used to define vascular aging and abnormal or disease-related arterial changes.